Functional expression of the endogenous Thy-1 gene and the transfected murine Thy-1.2 gene in rat basophilic leukemia cells - Dráberová, L; Dráber, P (European journal of immunology, 1991)
An interaction of MRC OX7 monoclonal antibody with Thy-1.1 antigen of rat peritoneal and pleural mast cells has been previously shown to induce rat mast cell activation (L. Dráberová, Eur. J. Immunol. 1989, 19: 1715). In the present study we analyzed the expression and function of the Thy-1 antigen in rat basophilic leukemia cells, clone RBL-2H3. Two RBL-2H3-derived cell lines with stable expression of murine Thy-1.2 antigen, after transfection of a genomic clone of murine Thy-1.2 or Thy-1.2 cDNA under the control of simian virus 40 promoter, were also analyzed. Direct radioantibody binding assays, indirect immunofluorescence studies and flow cytometry analyses revealed that both endogenous Thy-1.1 and transfected murine Thy-1.2 gene products were expressed on the surface of the cells under study. Analysis of the distribution of the Thy-1 antigen in situ in cells grown attached to tissue culture vessels located the Thy-1 predominantly in regions of cell-cell contacts. Incubation of RBL-2H3 cells with Thy-1.1-specific antibodies, or of the transfected cells with both Thy-1.1- and Thy-1.2-specific antibodies, induced a rapid early increase in the concentration of intracellular free calcium [( Ca2+]i) released from internal stores. Sustained increase of [Ca2+]i required the presence of Ca2+ in the extracellular medium. The increase in [Ca2+]i was followed by histamine release from the target cells. The combined data indicate that RBL-derived cells can be used as a useful model system for analysis of Thy-1 antigen-mediated activation of rat mast cells.
Keywords: Thy-1 Antigens; uvolňování histaminu; Antigens, Surface; akutní bazofilní leukemie; Histamine Release; Gene Expression; krysa rodu Rattus; Calcium; transfekce; mezibuněčná komunikace; nádorové buňky kultivované; Antibodies, Monoclonal; monoklonální protilátky; Leukemia, Basophilic, Acute; vápník; Cell Communication; antigeny Thy-1; zvířata; Rats; Animals; exprese genu; antigeny povrchové; Tumor Cells, Cultured; Transfection